Framework to Enhance Critical Information Literacy in University Libraries in Kenya - Mutegi, James Njue; Oyieke, Lilian; Ndiku, Mbenge T. (International Journal of Knowledge Content Development & Technology, 2026)
Purpose: This study investigated adopting a framework to enhance CIL in selected university universities in Kenya. CIL evaluates the effectiveness of Information Literacy (IL), disrupts unfair systems, and creates student- driven IL instruction. Methodology: A Descriptive survey research design was used to gather information on a framework to enhance CIL in selected university universities in Kenya. The research was carried out in fourteen university libraries in Kenya. The fourteen university libraries were purposely sampled because they had subscribed to electronic resources and KENET ICT infrastructure and had employed ICT and reference librarians. The target population was 14 University Librarians. The census approach involved all fourteen librarians in this research study. Data was collected on the interview schedule. Atlas. ti was used to analyze qualitative data. Findings: These findings show that university librarians associate CIL with information retrieval. In addition, the findings revealed that the librarians identified key codes of CIL, such as supporting users in access to information, user education, critical thinking, and user information resources. Based on these findings, the study proposes a CIL framework consisting of six steps: Awareness Creation, User needs Assessment and Information Gap, CIL Library Infrastructure, CIL infrastructure, Librarian Empowerment, User Empowerment, and CIL Evaluation.